2016
DOI: 10.1021/acs.jpcc.6b03855
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Small Alkanes on ZSM-5 Zeolites: Influence of Brønsted Sites

Abstract: The adsorption of a series of small alkanes was studied experimentally on H-ZSM-5 zeolites using calorimetric measurements in order to determine their interactions with the Brønsted sites. Differential heats measured on four ZSM-5 samples with different Si/Al 2 ratio and with different defect concentrations were found to depend strongly on the Brønsted-site density but not on the presence of defects. The interactions for CH 4 with the Brønsted sites were minimal but the effect was significant (up to 11 ± 2 kJ/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Alkane−OH hydrogen bond enthalpies have been previously calculated to range from 2 to 17 kJ/mol. 28 Studies of n-butane diffusion in the zeolite ZSM-5, where hydrogen bonds between n-butane and Brønsted acid sites were observed, reported an activation energy for diff usion of 18 ± 1 kJ/mol, 21,29 which is quite similar to the activation energy reported here for diffusion through hydroxylated UiO-66. Other prior work suggested that the diffusion of small alkanes through UiO-66 occurs via a "jump sequence mechanism", in which alkanes rapidly move within octahedral pores but become momentarily trapped once they enter the tetrahedral pores.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Alkane−OH hydrogen bond enthalpies have been previously calculated to range from 2 to 17 kJ/mol. 28 Studies of n-butane diffusion in the zeolite ZSM-5, where hydrogen bonds between n-butane and Brønsted acid sites were observed, reported an activation energy for diff usion of 18 ± 1 kJ/mol, 21,29 which is quite similar to the activation energy reported here for diffusion through hydroxylated UiO-66. Other prior work suggested that the diffusion of small alkanes through UiO-66 occurs via a "jump sequence mechanism", in which alkanes rapidly move within octahedral pores but become momentarily trapped once they enter the tetrahedral pores.…”
Section: Resultssupporting
confidence: 81%
“…20 Within those systems, surface hydroxyl groups have been suggested to act as Brønsted acid hydrogen bond donors to slightly more electronegative alkanes. 20,21 The complete disappearance of the free hydroxyl band at 3674 cm −1 suggests that butane can access every hydroxyl group within the MOF. Following exposure, the concentration of MOF-bound butane was tracked in real time as the molecules diffused through the sample and desorbed into the gas phase where they were efficiently removed from the UHV chamber.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other probe molecules used to investigate surface acidity using IR spectroscopy are carbon monoxide (CO), nitrogen (N 2 ) and ammonia (NH 3 ) detecting the vibrational modes of C^O triple bonds, N^N triple bonds and N-H bonds, respectively. Studies combining IR and solid-state 27 Al NMR, 32 TPD 33 or thermal gravimetric analysis (TGA) 16 established the same correlation between the total Al content and the number of Brønsted acid sites.…”
mentioning
confidence: 87%
“…Microcalorimetry, [14][15][16] temperature-programmed desorption (TPD), 17,18 infrared (IR) [19][20][21][22][23][24][25][26][27] and nuclear magnetic resonance (NMR) spectroscopy 17,28 are among other experimental techniques some of the most frequently used ones. A fundamental challenge of zeolite acidity characterisation is that different experimental techniques provide different aspects of the zeolite acidity, which includes type, number, location and strength of acid sites.…”
mentioning
confidence: 99%
“…HY zeolite has 12-membered ring connected supercages of 7.4×7.4 Å 24 , while HZSM-5 zeolite has 10-membered ring straight and zigzag pore channels of 5.3×5.6 and 5.1×5.5 Å 25 . Iglesia et al 14 reported that this different pore structure could change the activation barriers of C3H8 cracking.…”
Section: Introductionmentioning
confidence: 99%